2019
DOI: 10.5588/ijtld.17.0785
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community-based DOTS strategy on tuberculosis treatment success rates in Namibia

Abstract: Setting: Directly Observed Treatment Short-course is a key pillar of the global strategy to end tuberculosis. Objective: The effectiveness of community-based compared to facility-based DOTS on tuberculosis treatment success rates in Namibia was assessed. Methods: Annual tuberculosis treatment success, cure, completion and case notification rates were compared between 1996 and 2015 by interrupted time series analysis. The intervention was the upgrading by the Namibian government of the tuberculosis treatment st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…We believe this is the first study to qualitatively identify key factors influencing prescribing practices and NSTG compliance across disease areas building on assessments of guideline adherence in specific treatment and disease areas as well as ways to improve the content and pragmatism of national STGs among sub-Saharan African countries [10,[16][17][18]. This is a concern given the high prevalence of both infectious and non-infectious diseases in sub-Saharan Africa and their impact on morbidity, mortality and costs [5,[19][20][21][22][23][24][25][26][27]. The prescribing indicators were typically sub-optimal compared with the Namibia and WHO/INRUD standards, similar to other African countries [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…We believe this is the first study to qualitatively identify key factors influencing prescribing practices and NSTG compliance across disease areas building on assessments of guideline adherence in specific treatment and disease areas as well as ways to improve the content and pragmatism of national STGs among sub-Saharan African countries [10,[16][17][18]. This is a concern given the high prevalence of both infectious and non-infectious diseases in sub-Saharan Africa and their impact on morbidity, mortality and costs [5,[19][20][21][22][23][24][25][26][27]. The prescribing indicators were typically sub-optimal compared with the Namibia and WHO/INRUD standards, similar to other African countries [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…15 29 Conversely, the study result is comparable to a study reported from Mongolia, whereby patients who opted for CB-DOTS showed a higher cure rate than those who attended the FB-DOTS approach (89.9% vs 77.2%) 22 and a study in Namibia in which the cure rate was significantly increased with the implementation of CB-DOTS. 20 Our finding could be explained by the fact that the CB-DOTS option is more accessible to patients, as it is convenient and nearer to their home. 30 In addition, CB-DOTS is flexible in terms of time and place for patients to obtain DOTS service compared with the FB-DOTS approach.…”
Section: Discussionmentioning
confidence: 76%
“…13 Previous studies in different countries have shown that CB-DOTS is more effective than the FB-DOTS approach. [14][15][16][17][18][19][20] In the Jimma Zone, where this study was conducted, only 23% of the health posts provided TB treatment at the community level during the study period. To the best of our knowledge, a comparative study on CB-DOTS versus FB-DOTS delivery approaches has not been conducted in Southwest Ethiopia.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 6 , 7 , 20 Fortunately, with the adjustment of treatment strategies in recent years, there are declining trends in loss to follow up (LTFU) and increasing trends in the success rate of TB treatment. 21 , 22 Kibuule et al reported that since the expansion of facility-based DOTS programme to community-based DOTS programme in Namibia in 2005, 23 the mean annual treatment success rate increased by approximately 20% when comparing the pre-intervention (1996–2005) and the post-intervention (2005–2015) periods.…”
Section: Discussionmentioning
confidence: 99%